A leaf inoculation method for detection of Xanthomonas oryzae pv. oryzicola from rice seed - Xie, G.L.; Mew, T.W. (Scientific Societies, 1998)
A leaf-inoculation method for detecting Xanthomonas oryzae pv. oryzicola in rice seed was developed and tested. The method is based on inoculating leaf segments on agar with seed washings in a moist chamber. Freshness of inoculated leaf segments is maintained by addition of 75 to 100 ppm benzimidazole to the 1% water agar after sterilization. Using cells from pure cultures, the minimum inoculum concentration to initiate leaf streak lesions on the segments was found to be 103 CFU/ml. Inoculum prepared from seeds harvested from severely infected mother plants induced lesions typical of leaf streak, followed by bacterial ooze. With 4 g of seed, the incubation period was 3.5 days and bacterial ooze appeared within 5 days. The minimum amount of seed needed to detect the bacterium based on seed washings varied according to disease severity of the mother plants. The bacteria isolated from lesions on the leaf segments were confirmed as X. oryzae pv. oryzicola after bacteriological, serological, and Biolog tests were conducted. The results confirm that the detached-leaf method is as simple and reliable as the immuno-radiometric assay and inoculation on intact pot-grown rice plants in the greenhouse.